Atuação de bentonite e polivinilpolipirrolidona (PVPP) na clarificação de vinhos espumantes - Silva, Heber Rodrigues (2011)
The size and persistence of the bubbles is one of the characteristics pursued by consumers of sparkling wine. The perlage is closely linked to nitrogen products, usually proteins of low molecular weight. Furthermore, bentonite and polyvinylpolypyrrolidone (PVPP) are glues used both in cleaning up the base wine and the sparkling wines, in other words, the fermentation in bottles, and can even drag from the liquid the phenolic compounds. The aim of this study was to evaluate the action of these two clarifiers upon the perlage, a synonym for this type of wine quality. So sparkling wines were prepared, using nine treatments and three replications; the amount of polyvinylpolypyrrolidone and bentonite varied in each treatment and also a blank was made. It was analyzed total nitrogen, through Micro-Kjedahl, carbon dioxide, total phenols, oxygen, time that perlage lasts and some other classical physical-chemistry compounds. It was found that polyvinylpolypyrrolidone and bentonite additions were crucial to control turbidity of the sparkling wines; it was noted a decrease in total nitrogen when using increasing of both clarifiers. The treatments with polyvinylpolypyrrolidone alone reduced more the amounts of phenolic compounds when compared with those treated only with bentonite. This fait confirmed a higuer bounding between polyvinylpolypyrrolidone and phenols than between bentonite and phenols. The clarification reduced the time that perlage lasted in a direct relationship with the decrease of total nitrogen. Some treatments did not show a relation between carbon dioxide and perlage; perhaps the temperature that the sparkling wine was poured in the cup, the difference among the glass walls of the different cups or yet, the residues in the glass (from soap etc.) caused different sites of nucleation.